Characterization and design of the FutureGen 2.0 carbon storage site. (October 2016) - Gilmore, Tyler; Bonneville, Alain; Sullivan, Charlotte; Kelley, Mark; Appriou, Delphine; Vermeul, Vince; White, Signe; Zhang, Fred; Bjornstad, Bruce; Cornet, Francois; Gerst, Jacqueline; Gupta, Neeraj; et al.
Highlights: A full geologic characterization of a carbon storage site in Illinois is presented. A site-specific conceptual model and monitoring plan have been completed. U.S. EPA issued the four first-of-their-kind Class VI UIC permits for this project. Abstract: The objective of the FutureGen 2.0 Project was to demonstrate, at the commercial scale, the technical feasibility of implementing carbon capture and storage in a deep saline formation in Illinois, USA. Over approximately 5 years, the FutureGen Industrial Alliance, Inc. (Alliance) conducted a detailed site-selection process and identified a site for carbon sequestration storage in Morgan County, Illinois. A comprehensive geologic and hydrologic characterization of the storage site was conducted and included the collection of seismic data and the drilling and characterization of a stratigraphic borehole. The characterization data provided critical input for developing a site-specific conceptual model and subsequent numerical modeling simulations. The modeling simulations, coupled with upstream designs of the pipeline and power plant, supported the development of a detailed design that included the injection wells and associated control and monitoring infrastructure. The Alliance used all of these data to develop the required documentation to support the applications for four underground injection control (UIC) permits (one for each proposed well). In August 2014, the U.S. Environmental Protection Agency issued four, first-of-their-kind, Class VI UIC permits for carbon sequestration in the United States to the Alliance. This equated to one permit per planned injection well. The information and data generated under this project have been made publicly available through reports and publications, including this journal and others.